Endothelin-1 in systemic sclerosis - C. Pizzorni; A. Sulli; M.E. Secchi; M. Cutolo (PAGEPress Publications, 2011)
We evaluated endothelin-1 (ET-1) plasma levels in patients affected by primary Raynaud's phenomenon (PRP), as well as in patients with systemic sclerosis (SSc) and secondary Raynaud's phenomenon (SRP). Furthermore, ET-1 levels were investigated in SSc patients with different patterns of peripheral microvascular damage, as evaluated by nailfold videocapillaroscopy (NVC). Methods: 23 PRP patients, 67 SSc patients according to ACR criteria, and 23 healthy subjects were enrolled. SSc microvascular involvement was classified in three different patterns (Early, Active, and Late) by NVC, as previously described. Results: ET-1 was found significantly higher in both PRP and SRP, when compared with controls (median ±IQR: 3.3±2.8, 2.7±2.2, 2.0±2.2, respectively) (p=0.05). No statistically significant difference of ET-1 levels was observed between PRP and SRP patients. ET-1 was found higher in patients with Late NVC pattern, when compared with both Active and Early NVC patterns (median±IQR: 3.4±2.5, 2.4±2.2, 2.5±2.1, respectively), but without statistical significance. Patients with Late NVC pattern showed significantly higher ET-1 plasma levels than controls (p=0.03). No correlation was found between ET-1 levels and disease duration in both groups, as well as between ET-1 levels and age of patients. Conclusions: These data support previous studies, reporting increased ET-1 plasma levels in both PRP and SRP patients. Interestingly, patients with the Late NVC pattern of microangiopathy showed higher ET-1 plasma levels than controls. The high levels of ET-1 detected in the Late NVC pattern of microangiopathy might be related to the larger fibrotic involvement typical of the advanced stages of disease.